Pengaruh Penambahan Serat Ampas Tebu (Saccharum Officinarum L.) Terhadap Kekuatan Tekan Resin Komposit Nanofil - Fithriatusshalihah, Rizka; , drg. Noor Hafida W, Sp.KG; , drg. Budi Dewantari (2016)
Nanofill composite resin is a new formulation of nanomeric and nanocluster. Nanofill composite resin has a lower compressive strength rather than mikrohibrid and mikrofil composite. An effort to improve the compressive strength is by adding fiber material. There are two types of fiber, namely synthetic and non-synthetic fiber. One of examples from non-synthetic fiber is bagasse fiber. The aim of this research is, to know the effect by adding bagasse fiber towards compressive strength of nanofill composite resin. This research uses 27 samples of nanofill composite resin printer tool, compared into 3 variable groups. The group I is nanofill composite resin without fiber, group II is nanofill composite resin by using bagasse fiber, and group III is nanofill composite resin by using synthetic fiber (polyethylene) as a control group. The samples are submerged in aquades and incubationed for 24 hours by using temperature in 370C. Then the samples are tested in the compressive strength by using universal testing machine. The result data of this research is analyzed by using one way anova with 95% of confidence level. The research result shows the significance difference of compressive strength among three variable groups, that is p=0,000 (p<0,005). The nanofill composite resin by using polyethylene fiber has the higest compressive strength. The nanofill compressive resin by using bagasse fiber has the almost same compressive strength with composite resin by using polyethylene fiber. The conclusion of this research is, by adding bagasse fiber can effect the compressive strength and improve the compressive strength of nanofill composite resin.